2014
DOI: 10.1002/ijc.29151
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐155 deficiency enhances the recruitment and functions of myeloid‐derived suppressor cells in tumor microenvironment and promotes solid tumor growth

Abstract: Immune cells in tumor microenvironment play a prominent role in tumor progression and metastasis. represents an important player in innate and adaptive immunity by regulating differentiation, maturation and activation of macrophages, dendritic cells, B cells and T cells. However, the role of miR-155 expression in immune cells in solid tumor development is less elucidated. Our current study showed that both B16-F10 melanoma and Lewis lung carcinoma tumors grew much faster in bic/miR-155 knockout (miR-155 2/2 )… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
85
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(93 citation statements)
references
References 48 publications
2
85
2
Order By: Relevance
“…In addition, Qu et al [23] found that microRNA-155-5p is correlated with the invasion depth and TNM stage of colon cancer. The role of microRNA-155-5p has also been explored in [24] hepatoma-associated mesenchymal stem cells and regulating the tumor microenvironment [2527]. However, the role microRNA-155-5p has not been identified in ARDS.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Qu et al [23] found that microRNA-155-5p is correlated with the invasion depth and TNM stage of colon cancer. The role of microRNA-155-5p has also been explored in [24] hepatoma-associated mesenchymal stem cells and regulating the tumor microenvironment [2527]. However, the role microRNA-155-5p has not been identified in ARDS.…”
Section: Discussionmentioning
confidence: 99%
“…In a large number of cancers, several HIM are induced in response to hypoxia, including miR-67, miR-21, and the miR-Let7 family (18), we did not observe any effect on their expression under hypoxia in MDSC. It should be noted that although several miRNAs, including miR-155 (12,16), miR-494 (15), miR-223 …”
Section: Discussionmentioning
confidence: 99%
“…Liu and colleagues (15) have shown that miR-494 was required for the accumulation and functionality of tumor-derived MDSCs. Recently, Wang and colleagues (16) provided data indicating that miR-155 deficiency enhanced MDSCs function and MDSC recruitment in tumor microenvironment.…”
Section: Introductionmentioning
confidence: 99%
“…The tumor draining lymph nodes and tumors were collected, and cell populations were analyzed using flow cytometry as previously described (29). Briefly, cells were stained with anti-CD3 FITC, anti-CD4 APC or anti-CD8 APC, and anti-CD25 PE (Biolegend) in PBS containing 2% FBS for 30 min at 4 °C.…”
Section: Methodsmentioning
confidence: 99%